2021
DOI: 10.3389/fphys.2021.642922
|View full text |Cite
|
Sign up to set email alerts
|

A High Percentage of Patients Recovered From COVID-19 but Discharged With Abnormal Liver Function Tests

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) pandemic has become the most severe global health issue. Abnormal liver functions are frequently reported in these patients. However, liver function abnormality was often overlooked during COVID-19 treatment, and data regarding liver functions after cure of COVID-19 is limited. This study aimed to reveal the changes of liver function tests (LFTs) during hospitalization, and its clinical significance in patients with COVID-19.MethodsIn this retrospective, bi-center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Moreover, similar to other studies, no differences were observed between patients with or without abnormal LFT related to medications that were indicated prior to admission [20]. Finally, as was suggested by other authors, it is possible that patients with ALEx2 might present a higher percentage of undiagnosed chronic liver disease [10]. Prior studies showed that patients with underlying liver disease have a higher percentage of liver test abnormalities and decompensated cirrhosis, which were associated with severe COVID-19 [18,26].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, similar to other studies, no differences were observed between patients with or without abnormal LFT related to medications that were indicated prior to admission [20]. Finally, as was suggested by other authors, it is possible that patients with ALEx2 might present a higher percentage of undiagnosed chronic liver disease [10]. Prior studies showed that patients with underlying liver disease have a higher percentage of liver test abnormalities and decompensated cirrhosis, which were associated with severe COVID-19 [18,26].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, cholangiocytes express high levels of ACE2 and could be the target of SARS-CoV-2 in the liver. Nevertheless, ALP was not usually as elevated in our or other studies as it might be expected [ 10 , 24 ]. A proposed mechanism that has gained popularity based on preliminary data includes the cytokine storm associated with systemic inflammatory response syndrome, especially in patients with severe COVID-19 infection [ 19 , 25 ].…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“… 13 In addition, many studies have highlighted the correlation of abnormal liver functions with severe COVID‐19 disease. 14 , 15 , 16 , 17 , 18 In this report, COVID‐19 was mainly studied in male patients. This could be attributed to the nature of the kingdom, in which the primary workers are male.…”
Section: Discussionmentioning
confidence: 99%